음악요법과 소음차단요법이 수술 후 통증, 진통제 투여량, 회복실 체류시간 및 만족도에 미치는 효과 비교 - 서은주; 윤혜상 (Journal of Korean biological nursing science, 2015)
Purpose: This study compared the effect of music and noise blocking on the vital signs, postoperative pain, analgesic use, length of stay in the Post Anesthesia Care Unit (PACU) and satisfaction after a laparoscopic colectomy. Methods: This randomized controlled trial was performed in a 555-bed National Cancer Center, from February 13 through May 31, 2012. Subjects consisted of 69 patients who underwent a laparoscopic colectomy under general anesthesia, and were recruited by informed notices. The inclusion criteria were patients between the ages of 35-75, with an American Society Anesthesiologist physical classification I or II. The subjects were randomly allocated to three groups; music therapy group (MTG), noise blocking group (NBG) and control group (CG). Collected data were analyzed using Repeated measures ANOVA, one-way ANOVA and Kruskal-Wallis test through IBM SPSS (Version 19.0). Results: There were no significant differences in vital signs among the three groups. Postoperative pain in MTG (p<.05) and NBG (p<.05) was significantly decreased compared to CG. The amount of analgesics (p=.030) and length of stay at PACU (p=.021) in MTG was significantly decreased compared to NBG or CG; satisfaction in MTG and NBG was significantly higher compared to CG. Conclusion: Music seems to reduce postoperative pain, the amount of analgesics, and the length of stay at PACU. Therefore, music therapy is considered to be included in nursing intervention for postoperative patients at PACU.